2016
DOI: 10.1177/2233865916632089
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the smart cities agenda in India

Abstract: With the election of Prime Minister Narendra Modi in 2014, urban-led economic growth in India was firmly framed around a vision of 'smart cities', an ambiguous concept, which promotes the integration of information and communication technologies in cities to improve economic growth, quality of life, governance, mobility and sustainability. Given its current policy importance, this article examines how the smart cities agenda in India has emerged, what it has encompassed and its potential for transformative urb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 33 publications
0
41
0
3
Order By: Relevance
“…Appendix A provides more detailed information about the 56 studies including country/initiative studied, method of the study and the aims/objectives of the study. Geographical locations (country/continent) of the included studies by descending order (based on the number of studies identified) India [28,[32][33][34][35][36][37][38][39][40][41][42][43][44][67][68][69][70]79] China [45][46][47][48][49][50][51][52][53]71,76,80] Indonesia [54][55][56][57] Brazil [3,58,72] Malaysia [59][60][61] Vietnam [62,73] Mexico [63] Turkey [78] Egypt [81] Romania [64] Nepal [65] ...…”
Section: Study Contexts and Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Appendix A provides more detailed information about the 56 studies including country/initiative studied, method of the study and the aims/objectives of the study. Geographical locations (country/continent) of the included studies by descending order (based on the number of studies identified) India [28,[32][33][34][35][36][37][38][39][40][41][42][43][44][67][68][69][70]79] China [45][46][47][48][49][50][51][52][53]71,76,80] Indonesia [54][55][56][57] Brazil [3,58,72] Malaysia [59][60][61] Vietnam [62,73] Mexico [63] Turkey [78] Egypt [81] Romania [64] Nepal [65] ...…”
Section: Study Contexts and Characteristicsmentioning
confidence: 99%
“…Budget constraints and financing issues are among the most significant barriers identified in smart city development in developing countries [40,41,43,48,67,74,78,81]. Budget constraints restrain the ability of governments to develop smart cities, even though smart cities are projected to be more cost-effective in the longer term [40].…”
Section: Budget Constraints and Financing Issuesmentioning
confidence: 99%
See 3 more Smart Citations